Bridging the Divide: Legal and practical issues in rail goods transit between Thailand and Laos - Seehawattana, Acharaporn; Weeraphan, Paramaporn; Kumtrai, Damorn (Journal of Ecohumanism, 2025)
This study investigates rail-based goods transit's regulatory and operational challenges between Thailand and the Lao People's Democratic Republic (PDR). The research specifically (1) Analyzes the legal frameworks governing rail freight transit in Thailand and Lao PDR; (2) Identifies inconsistencies and practical hurdles impacting cross-border transit, including customs processes, electronic system integration, and transit guarantees; (3) Proposes actionable solutions for improving efficiency and harmonization in goods transit between the two countries. Thai regulations such as the Customs Act B.E. 2560 (2017) and the Customs Department Notifications No. 169/2563 and No. 185/2564 are compared with Lao PDR’s legislative frameworks like the Tax Law, revealing critical gaps. Key practical issues include differing transit practices, train scheduling conflicts, and incompatible rail gauges (meter vs. standard). Solutions include quota negotiations for rail wagons, streamlined fee structures for customs-related services, and infrastructure support for rail gauge transitions. This research offers policy recommendations to enhance bilateral cooperation and streamline rail transit operations.